Electromagnetic and Thermal Co-Analysis of an Implanted Dipole Antenna - Ala Alemaryeen; Sima Noghanian (IEEE Open Journal of Antennas and Propagation)
Implanted wireless biomedical devices represent a significant advancement in medical technology, offering continuous monitoring and targeted therapy. Antenna design for these devices requires careful modeling to ensure efficiency and safety, addressing challenges such as tissue heating and compliance with safety regulations. Specific absorption rate (SAR) analysis, commonly used to ensure safety, often overlooks factors that influence tissue temperature and heat transfer. Understanding heat generation within tissues due to factors like location, orientation, and radiation power is crucial for optimizing device performance. Simulation-driven design and additional computational and experimental studies are essential for patient safety and effective device evaluation. This article focuses on examining tissue temperature elevation near implanted antennas, specifically a simple dipole antenna, to identify design parameters that significantly impact thermal performance. Key parameters include body phantom type and size, thermal boundary conditions, bioheat model parameters, implantation depth, antenna orientation, and input power. The study aims to provide guidelines for designers on optimizing antenna parameters to accurately predict and manage biological tissue heating. It was found that the size of the phantom, blood perfusion, volume thermal losses, antenna orientation, and input power constitute the major effects on tissue heating. An experimental setup was used to help understand the effect of the antenna’s input power on the temperature distribution in the surrounding high dielectric constant material. A dipole antenna was inserted inside a distilled water tank, and the temperature was measured at three reference points surrounding the antenna. Simulation and measurement results were in good agreement supporting the proposed methodology.